2022-RA-717-ESGO Establishment of peritoneal dECM scaffolds for 3D culture of ovarian cancer organoids. (20th October 2022) - Gjerde, Christiane Helgestad; Langer, Anika; de Garibay Ponce, Gorka Ruiz; Kleinmanns, Katrin; Dongre, Harsh Nitin; Mustafa, Rammah Elnour; Berger, Constantin; Willoughby, Robert; de Jalón, Elvira García; Gultekin, Okan; Bozluolcay, Erdem; Davidson, Ben; et al.
Abstract : Introduction/Background: Recently, ovarian cancer organoids have been developed, showing promising advantages compared to traditional 2D cell culture and mouse models. Organoids are 3D cell cultures and conventionally cancer cells are embedded in a gel composed of extracellular matrix (ECM) proteins. These gels do not fully mimic the native ECM of a human tumour. Natural ECM scaffolds can be generated by decellularization of different tissues (dECM). The aim of this study is to generate and characterize peritoneal extracellular matrix (PerMa) scaffold and compare to already established small intestinal submucosal scaffold (SIS). The PerMa scaffold will be used in the establishment of an ovarian cancer organoid platform. Methodology: A protocol for decellularization of porcine and human peritoneum was developed. The permeability of the scaffolds was assessed with diffusion assay. Multiphoton microscopy and rheological analyses were done to assess the collagen structure and biophysical properties of the scaffolds. Cell cultures of ovarian cancer cell lines and primary patient cells were set up. Results: The decellularization was validated with histology and DNA quantification. Cell cultures were successfully established with ovarian cancer and fibroblast cell lines and primary patient cells. Growth characteristics differed significantly on PerMa and SIS. We went on to investigate whether there are structural or biophysical differences that might explain this. We found no differences in the permeability to low (4 kDa) or high (40 kDa) molecular weight molecules between SIS and PerMa, but multiphoton microscopy revealed different organization of collagen fibres. Further, rheological analyses showed differences in elasticity (storage modulus, G´) and viscosity (loss modulus, G´´). Conclusion: We have established and characterized a 3D model of ovarian cancer that better represents the tumour microenvironment. In the future we will use this model system to establish patient-derived ovarian cancer organoids with potential application for tumour biology research and personalized medicine.